Efektivitas Modul Optika Berbasis Problem Solving dalam Meningkatkan Higher Order Thinking Skills Calon Guru Fisika - Wahyudi Wahyudi; Nurhayati Nurhayati; Dwi Fajar Saputri (Postgraduate, University of Mataram, 2022)
This study aimed to identify the effectiveness of using physics-based problem-solving modules in improving prospective physics teacher students' higher-order thinking skills (HOTS). The experimental method has been used in designing the one Group Pretest-Posttest Control Groups. The research sample was all students who took the optics course. HOTS data was measured using a two-tier multiple-choice test instrument, and problem-solving ability data was measured using a Likert scale questionnaire. Data analysis was performed using descriptive and inferential statistics, including the N-Gain test, effect size, and Kruskal Wallis. The results showed that (1) there was an increase in student HOTS after the problem-solving-based module was applied by 0.42 in the medium category, and an increase occurred in all aspects of HOTS, including analyzing, evaluating, and creating; (2) the effect of problem-solving ability on students' HOTS; and (3) the effectiveness of problem solving-based modules is 2.36 in the very effective category. The results of the study can be concluded that the problem-solving-based optical module that has been designed is very effective in increasing students' HOTS and problem-solving abilities to support student success in learning optics